2014
DOI: 10.1094/cchem-04-13-0062-r
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic and Body Fat–Lowering Effects of Giant Embryo Brown Rice (Seonong 17 and Keunnunjami) in High‐Fat‐Fed Mice

Abstract: The effects of giant embryo brown rice Seonong 17 and Keunnunjami, in comparison with that of ordinary normal brown rice, on the body weight and lipid profile in mice under a high‐fat diet condition were investigated. The animals were fed with experimental diets for eight weeks: normal control, high fat (HF), and high fat supplemented with normal brown rice, Seonong 17 rice, or Keunnunjami rice powder. Their body and fat weights, lipid profiles, lipogenic enzyme activities, and adipokine concentrations were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…The antiobesity and cholesterol lowering effects of BR varied depend on rice cultivar, mutant, or variety. For example, two giant embryo BR mutants, namely Seonong 17 and Keunnunjami, showed greater hypolipidemic and body fat lowering effects in mice than those of normal BR, suggesting them as ingredients for making of functional foods with antiobesity and hypolipidemic effects (Chung et al., ).The germination improved the potential antiobesity and cholesterol lowering effects of BR. Diets containing 50% GBR were more effective in the reduction of weight gain and improving lipid parameters, ox‐low‐density lipoprotein, and F2‐isoprostane in hypercholesterolemia‐induced rats than BR; while WR supplemented diets showed a negative effect.…”
Section: Potential Health Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiobesity and cholesterol lowering effects of BR varied depend on rice cultivar, mutant, or variety. For example, two giant embryo BR mutants, namely Seonong 17 and Keunnunjami, showed greater hypolipidemic and body fat lowering effects in mice than those of normal BR, suggesting them as ingredients for making of functional foods with antiobesity and hypolipidemic effects (Chung et al., ).The germination improved the potential antiobesity and cholesterol lowering effects of BR. Diets containing 50% GBR were more effective in the reduction of weight gain and improving lipid parameters, ox‐low‐density lipoprotein, and F2‐isoprostane in hypercholesterolemia‐induced rats than BR; while WR supplemented diets showed a negative effect.…”
Section: Potential Health Benefitsmentioning
confidence: 99%
“…The concentration of these nutrients and bioactive compounds may vary depending on influences such as rice variety, production environment or geographical origin, and postharvest treatments or processing conditions. The whole BR grain, germinated BR grain (GBR), or their derived extracts and fractions have shown several potential health benefits such as antioxidant, antidiabetic, anticancer, neuroprotective, and cholesterol lowering effects (Chompoopong et al., ; Chung, Rico, Lee, & Kang, ; Li, Chou, & Shih, ; Lim, Yong, Mohtarrudin, & Loh, ; Masuzaki et al., ; Pang et al., ). Therefore, the objective of this work is to review the last updates in research performed for purposes of evaluating of nutritional quality and potential health benefits of the whole BR to provide recent information to interested researchers and consumers, which may help in promotion of the whole BR consumption as a promising functional food and for its potential contribution to human well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…Chung et al (1) recently reported that Keunnunjami rice contains relatively high amounts of phenolics and flavonoids and has strong antioxidant capacity. Moreover, it has been reported that dietary feeding of this pigmented giant embryo rice reduced the body weight and improved the lipid metabolism in high fat diet-fed mice (3).…”
Section: Discussionmentioning
confidence: 99%
“…It contains high amounts of natural antioxidant compounds and has strong antioxidant capacity (1, 2). A recent investigation on this rice cultivar revealed that it could modulate the lipid metabolism and lower the body fat in high-fat diet-fed mice (3). An instant rice made from a combination of this pigmented giant embryo cultivar and ordinary white rice has also been shown to reduce the lipid levels and body weight in high fat diet-fed mice (4).…”
mentioning
confidence: 99%
“…Keunnunjami rice is a new blackish-purple pigmented cultivar with a giant embryo that was developed in Korea through conventional breeding. This pigmented rice was reported to contains high levels of antioxidant compounds and exhibit strong anti-obesity, hypolipidemic, and antioxidant properties [ 1 2 3 ]. Pigmented rice varieties, particularly those with dark-colored pericarps such as black and purple rice, are known for their health-promoting effects and functional activities, owing to the high contents of flavonoids, phenolic compounds, and anthocyanins [ 4 5 ].…”
Section: Introductionmentioning
confidence: 99%